A novel anti-infective molecule nesfactin identified from sponge associated bacteria Nesterenkonia sp. MSA31 against multidrug resistant Pseudomonas aeruginosa. (August 2021) - Kiran, George Seghal; Sajayan, Arya; Gopal Priyadharshini,; Balakrishnan, Aarthy; Prathiviraj, R; Sabu, Abdulhameed; Selvin, Joseph
Abstract: Overuse of antibiotics coupled with biofilm-forming ability has led to the emergence of multi-drug P. aeruginosa strains worldwide. Quorum sensing is a bacterial cell-cell communication system that regulates the expression of genes, including virulence factors, through production of acyl-homoserine lactones (AHLs) in Pseudomonas aeruginosa . The phenotypic expression of virulence factors in P. aeruginosa is mediated by quorum sensing systems (las and rhl). In this study an anti-infective molecule produced by a marine actinomycetes Nesterenkonia sp. MSA31 was elucidated as lipopeptide by NMR and LC-MS/MS analysis. The new lipopeptide molecule was named Nesfactin. This molecule effectively inhibited virulence phenotypes including production of hemolysin, protease, lipase, phospholipase, esterase, elastase, rhamnolipid, alginate, and pyocyanin, as well as motility and biofilm formation in P. aeruginosa . The high-performance thin layer chromatography (HPTLC) analysis revealed that the lipopeptide (50 μg/mL) inhibited production of the AHLs produced by the las and rhl quorum sensing systems (3-oxo-C12-HSL and C4-HSL, respectively). Docking analysis showed the binding affinity of the ligand towards the quorum sensing receptor molecules. The confocal laser scanning microscopy images showed the anti-biofilm effect of lipopeptide against P. aeruginosa. Nesfactin based hydrogel showed a significant antibiofilm effect on the catheter. This study suggests that the lipopeptide may be an effective anti-virulence treatment for Pseudomonas aeruginosa infections. Highlights: The anti-infective molecule produced by marine bacteria MSA31 was elucidated as –Leu/Ile-Leu/Ile -Asp-Val-Leu/Ile –Leu/Ile -Phe-HFA. The anti-infective molecule effectively controls virulence of multidrug resistant Pseudomonas aeruginosa. The compound MSA31 (50 μg/mL) inhibited production of the AHLs produced by the las and rhl quorum sensing systems. Docking analysis showed the binding affinity of the ligand towards the quorum sensing receptor molecules. Nesfactin based hydrogel showed significant antibiofilm effect on catheter.